The Urgence of State Administrative Science Education Among Students of STISIP Syamsul Ulum Sukabumi - Cepi Hanapia (Jurnal Mantik, 2021)
Basically, state administration science education is education whose establishment and implementation is inspired by the spirit of multiculturalism, in order to realize a harmonious life. Specifically, education in multicultural state administration is education based on Islamic principles that want to explore differences as a necessity. So the results of the study explain that administrative science education has an influence on patterns and understanding. Organizational culture is a set of values, beliefs and principles adopted by an organization that underlies the management system that applies in it and is used as a behavioral guide for members of the organization. A strong organizational culture gives employees a clear understanding of the tasks assigned by an organization, has a great influence on the behavior of its members.